AI-BASED HOTEL INFORMATION SYSTEM TO ENHANCE CUSTOMER EXPERIENCE AND FOSTER LOYALTY AT SYARIAH HOTELS IN BANDUNG - Yayan Sugiarto; Rika Solihah; Amalia Juliana Monika Intan (Media Bina Ilmiah, 2025)
This study aims to examine the role of AI-Based Hotel Information Systems in enhancing customer experience and fostering loyalty in Syariah Hotels in Bandung. Using a quantitative research approach, the study employs a causal-effect design to investigate these relationships. The population includes guests from 11 Syariah Hotels in Bandung, with 220 customers serving as respondents, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that (1) AI-based systems significantly influence customer experience, (2) AI systems directly foster loyalty customer, (3) experience directly impacts loyalty, and (4) customer use mediate the relationships between AI-based systems and customer loyalty. The study highlights the importance of integrating AI technologies to improve service personalization and operational efficiency. Future research could explore similar models in broader contexts or other industries.